1239 Cantú syndrome; another differential diagnosis for mucopolysaccharidosis phenotype – a case study. (17th August 2022) - ,; Kini, Usha; Anand, Geetha
Abstract : Aims: Introduction: Cantú syndrome is a rare genetic disorder characterized by congenital hypertrichosis, osteochondrodysplasia, distinctive facial characteristics, and cardiac abnormalities. When initial genetic panel for mucopolysaccharidoses (MPS) is negative, genetic testing for Cantú syndrome should be included in the extended genetic panel, since these two clinical entities share certain phenotypic characteristics. We present a case of Cantú syndrome that was initially investigated as for MPS. Methods: Case Study: A 4-year-old boy was referred for a paediatric assessment to rule out MPS since he had coarse facial characteristics. He was born at 37 weeks of gestation with birth weight of 3.6kg. He had undergone an umbilical hernia repair and adenoidectomy for sleep apnoea in the past. He had mild coarse facial features, bilateral epicanthic folds, a broad nasal bridge, a thick lower lip, and hypertrichosis. His weight and occipitofrontal circumference were above 99 th centile. He did not show features of skeletal dysplasia clinically and he did not have mobility issues. A Grade 3 systolic murmur was identified. He did not have hepatosplenomegaly on clinical assessment. His neurodevelopment was age appropriate at the time of the assessment. Results: The 2D-echocardiogram confirmed that he had a patent ductus arteriosus (PDA). There was no cardiomegaly or aortic root abnormality, and cardiac functions were normal. There was mild hepatomegaly detected on an ultrasound scan. Rest of the viscera did not show enlargement. He was investigated for MPS. Urinary glycosaminoglycan excretion was within normal limit. A rapid whole exome sequencing (WES) did not identify any MPS genes, but it detected a variation in one copy of ABCC9 (ATP- binding cassette subfamily C member 9) gene, leading to the diagnosis of Cantú syndrome. WES of parents identified that the father of the child had the same gene mutation, and mother's testing was normal. The father had similar facial characteristics and had undergone umbilical hernia repair in childhood. The index child and the father are under follow up given the cardiac implications. Conclusion: Discussion: Cantú syndrome, also known as hypertrichotic osteochondrodysplasia is a rare clinical entity. 97% of reported cases are due to mutations in ABCC9 gene. The rest of the cases are mainly due to mutations in KCNJ8 gene, and one case has been reported due to monosomy 1p36. ABCC9 encodes a superfamily of transporter proteins known as ATP-binding cassette (ABC) Proteins which functions as potassium channels in cardiac, skeletal, and vascular smooth muscles. Mutations of this gene are described in association with Cantú syndrome, Intellectual disability and myopathy syndrome, Familial atrial fibrillation, and Familial dilated cardiomyopathy. Both Cantú syndrome and MPS share similar clinical features including coarse facies, hypertrichosis, skeletal abnormalities, obstructive sleep apnoea, umbilical hernia, and cardiac abnormalities. Clinical differentiation between these two entities can be difficult, especially the milder phenotypes. Therefore, during evaluation of a child with MPS phenotype, it is important to extend the genetic testing towards Cantú syndrome, if MPS gene mutations are negative.